Code Mixing in Maudy Ayunda's YouTube Video "Life without social media would be happier” Maudy Ayunda's Booklist.: Code Mixing - Putri Suliani Br Saragih; Andrianus Andrianus Prananta Barus; Mulyadi (JALC : JOURNAL OF APPLIED LINGUISTIC AND STUDIES OF CULTURAL, 2024)
Currently, the use of the internet and gadgets and social media cannot be separated from everyday life. Behind the convenience offered by sophisticated technology, such as gadgets and social media, it has a negative impact and is detrimental to its users, one of which is addiction. Addiction starts from the production of dopamine in the brain which is triggered by likes, retweets, shares and emoticon reactions from other social media users who interact on their social media accounts. One of the Indonesian artists and singers, Maudy Ayunda, once discussed the book Digital Minimalist on her personal YouTube page. Maudy Ayunda discusses "Life without social media = happier?! Maudy Ayunda's Booklist.” The use of language in society in this era is more diverse. The use of language in society in this era is more diverse. With this diversity, it is possible for someone to change the language they use to another language when communicating. This phenomenon is called code switching and code mixing. One of them is in a video uploaded by Maudy Ayunda. This research aims to analyze the language code mixing used by Maudy Ayunda in the YouTube video entitled "Life without social media = happier?! Maudy Ayunda's Booklist.” The research method is descriptive qualitative research. From the analysis results, there are two languages ​​used in YouTube videos, namely Indonesian and English. The use of these two languages ​​creates code mixing in the video. There are twenty-five data on the code-mixing phenomenon. The code mixing in the YouTube video is due to the speaker's background being bilingual.